Evidence for negative selection of gene variants that increase dependence on dietary choline in a Gambian cohort - Silver, M.J.; Corbin, K.D.; Hellenthal, G.; Costa, K.A. da; Domínguez Salas, Paula; Moore, S.E.; Owen, J.; Prentice, A.M.; Hennig, B.J.; Zeisel, S.H. (Wiley, 2015)
Choline is an essential nutrient, and the amount needed in the diet is modulated by several factors. Given geographical differences in dietary choline intake and disparate frequencies of single-nucleotide polymorphisms (SNPs) in choline metabolism genes between ethnic groups, we tested the hypothesis that 3 SNPs that increase dependence on dietary choline would be under negative selection pressure in settings where choline intake is low: choline dehydrogenase (CHDH) rs12676, methylenetetrahydrofolate reductase 1 (MTHFD1) rs2236225, and phosphatidylethanolamine-N-methyltransferase (PEMT) rs12325817. Evidence of negative selection was assessed in 2 populations: one in The Gambia, West Africa, where there is historic evidence of a choline-poor diet, and the other in the United States, with a comparatively choline-rich diet. We used 2 independent methods, and confirmation of our hypothesis was sought via a comparison with SNP data from the Maasai, an East African population with a genetic background similar to that of Gambians but with a traditional diet that is higher in choline. Our results show that frequencies of SNPs known to increase dependence on dietary choline are significantly reduced in the low-choline setting of The Gambia. Our findings suggest that adequate intake levels of choline may have to be reevaluated in different ethnic groups and highlight a possible approach for identifying novel functional SNPs under the influence of dietary selective pressure.